The Influence of President Joko Widodo's Instagram Content on Beginner Voters Participation in the 2019 General Elections - Marsha Ruth Handoko; Yolanda Stellarosa (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
Instagram is a social media that is currently becoming a lifestyle trend and is in demand by the community. With the advantages of Instagram which is a photo and video posting service, Instagram is not only used for fun but is also used as a source of political information. One of the uses of Instagram content as a source of political information was carried out by President Joko Widodo. In the 2019 election, for the second period, Joko Widodo (Jokowi) ran for the Republic of Indonesia presidential candidate together with Ma'ruf Amin. The use of Jokowi's Instagram was an effort in conveying his political messages to attract the public, especially beginner voters. This study aims to determine whether there is an influence and how much is the influence of Jokowi's Instagram content on the participation of beginner voters in the 2019 general election. This research uses a quantitative method and distributed 96 questionnaires to followers of Jokowi’s Instagram account. Hypotheses testing has been done by doing regression tests, coefficient of determination and f-test. The result of linear regression has been indicated by equation Y=10,764 + 1,353X, with the results of hypotheses testing. The result showed that the variable of @jokowi Instagram content has a significant impact on the participation of beginner voters, with a contribution of 64,5%. It can be concluded that Joko Widodo’s Instagram content has a significant impact on the participation of beginner voters in the 2019 general election.